SARS-CoV-2 infection: efficacy of extensive vaccination of the healthcare workforce in a large Italian hospital - Coggiola, Maurizio; Clemente, Giuseppe; Frammartino, Roberto; Grillo, Eugenio; Corradi, Alessio; Corezzi, Michele; Kakaa, Omar; Paradisi, Ettore; Tuffanelli, Alessandro; Alfonso Pensamiento, Maria Carolina; Godono, Alessandro; Pira, Enrico (La Medicina del Lavoro, 2021)
Background: A prospective observational study involved 13,787 Health Care Workers (HCWs) of a large hospital to assess the effectiveness of a SARS-CoV-2 mRNA vaccine. Methods: The daily incidence of infections was estimated from 1st October 2020 to 30th April 2021 and compared with that of the province of Turin (2.26 million). In the middle of this period, a mass vaccination began among HCW, and its effect was assessed. Results: In the first half-period, 1,163 positive HCWs were observed, the average daily incidence rate per 100,000 being 79.58 (± 15.58; 95% CI) compared to 38.54 (± 5.96; 95% CI) in the general population (p